Edukasi pemanfaatan media sosial untuk berbisnis pada siswa SMA Negeri 2 Kabupaten Sorong: Education of social media use for business to student in SMA Negeri 2, Sorong Regency - Nur A. Khairunisa; Sabaria; Tri Danuwijaya (Fakultas Peternakan Universitas Papua, 2023)
ABSTRACT Social media is an important tool for almost all lines in society, including being used for business. This community service program is motivated by the large number of students who own and use social media, and mostly only as a channel to communicate with friends and family. In fact, the function of social media has become increasingly widespread, including for business purposes. This community service program aims to add to the positive benefits of social media owned by SMA Negeri 2 Sorong Regency students, namely for online business activities. Discussion of social media in this activity was limited to Instagram. This educational activity is carried out in the form of lectures and questions and answers. The results of this community service activity received a positive response from the students, this was shown by the enthusiasm of the students in participating in this lecture and the many questions asked by students regarding the use of social media for doing business. Keywords: Instagram marketing; Online business; Social media ABSTRAK Media sosial adalah sarana penting pada hampir semua lini dalam masyarakat, termasuk dapat dimanfaatkan untuk berbisnis. Program pengabdian masyarakat ini dilatarbelakangi oleh banyaknya para siswa yang memiliki dan menggunakan media sosial, dan kebanyakan hanya sebagai saluran untuk berkomunikasi dengan teman dan keluarga. Padahal sebenarnya fungsi media sosial telah menjadi semakin luas, termasuk untuk sarana berbisnis. Program pengabdian pada masyarakat ini bertujuan untuk menambah manfaat positif dari media sosial yang dimiliki siswa-siswi SMA Negeri 2 Kabupaten Sorong, yaitu untuk kegiatan berbisnis online. Pembahasan media sosial dalam kegiatan ini hanya terbatas pada instagram. Kegiatan edukasi ini dilakukan dalam bentuk ceramah dan tanya jawab. Hasil kegiatan pengabdian masyarakat ini mendapat respon positif dari para siswa-siswi, hal ini ditunjukkan oleh antusias para siswa-siswi dalam mengikuti ceramah ini dan banyaknya pertanyaan yang diajukan para siswa terkait pemanfaatan media sosial untuk berbisnis. Kata kunci: Bisnis online; Instagram marketing; Media sosial